2016
DOI: 10.1186/s12885-016-2256-7
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing equity in cancer care: implementation, challenges and preliminary findings of a public cancer referral center in rural Rwanda

Abstract: BackgroundCancer services are inaccessible in many low-income countries, and few published examples describe oncology programs within the public sector. In 2011, the Rwanda Ministry of Health (RMOH) established Butaro Cancer Center of Excellence (BCCOE) to expand cancer services nationally. In hopes of informing cancer care delivery in similar settings, we describe program-level experience implementing BCCOE, patient characteristics, and challenges encountered.MethodsButaro Cancer Center of Excellence was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…In 2012 Rwanda opened a cancer centre, primarily to serve the rural poor. This is a partnership between the Ministry of Health, academics and not-for-profit organisations (Tapela et al, 2016).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In 2012 Rwanda opened a cancer centre, primarily to serve the rural poor. This is a partnership between the Ministry of Health, academics and not-for-profit organisations (Tapela et al, 2016).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Recognizing the vast differences in access to care for rural versus urban‐dwelling Rwandans, the BDH/BCCOE was established as a new center for quality cancer care within the country. In the facility’s first 2 years, over 2000 patients were treated for various cancers; among this population, gastric cancer was identified as the sixth most common solid, nonskin cancer tumor . In 2014, a 1‐year observational study at two Rwandan referral hospitals demonstrated that out of 82 total patients with GOO, over two‐thirds were diagnosed with gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Both systems continue to benefit from the collaborative approach through ongoing development by global communities of practice and support. These solutions have built‐in flexibility that enables incorporation of functionalities, data elements, and indicators for other programs, including cervical cancer . The capacity for automation of indicator data reporting from the patient level (OpenMRS) to the subnational and national levels (DHIS 2) reduces burden and enhances the quality and timely availability of data for monitoring, as seen in HIV/AIDS and other programs .…”
Section: Recent Advances and Promising Practicesmentioning
confidence: 99%
“…Processes such as probabilistic record linkage have also been successful in linking cervical cancer data across disparate systems to create ad hoc longitudinal patient records . These models can be evaluated to determine feasibility for local implementation, and capacity to serve cervical cancer data needs …”
Section: Recent Advances and Promising Practicesmentioning
confidence: 99%
See 1 more Smart Citation